Analisis Pengelolaan Arsip Inaktif pada LKPP - Amanda Azhari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Kajian dan Penelitian Umum, 2023)
Archives play an important role in the operational activities of an organization as a source of information and memory center for the organization or company, but the existence of archives is sometimes less noticed, even ignored. The aim of this research is to analyze the management of inactive archives at the National Public Procurement Agency (LKPP). This research is descriptive research with a qualitative approach. Data collection techniques used in research are through observation, interviews and documentation. The population and sample in this research are employees who are directly involved in managing inactive records at LKPP. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The research results show that the management of inactive archives in LKPP has been running quite well. Management of inactive archives at LKPP includes storing inactive archives, maintaining archives and depreciating archives. However, there are several obstacles that hinder the management of inactive archives, namely lack of Human Resources (HR), limited archive space, lack of understanding regarding the management of inactive archives, and lack of leadership commitment. It is recommended that LKPP recruit workers who meet the required criteria, add or maximize existing facilities and infrastructure, and involve leadership directly in managing inactive records.